2D resistivity imaging and magnetic survey for characterization of thermal springs: A case study of Gergedi thermal springs in the northwest of Wonji, Main Ethiopian Rift, Ethiopia. (September 2017) - Abdulkadir, Yahya Ali; Eritro, Tigistu Haile
Abstract: Electrical resistivity imaging and magnetic surveys were carried out at Gergedi thermal springs, located in the Main Ethiopian Rift, to characterize the geothermal condition of the area. The area is geologically characterized by alluvial and lacustrine deposits, basaltic lava, ignimbrites, and rhyolites. The prominent structural feature in this part of the Main Ethiopian Rift, the SW -NE trending structures of the Wonji Fault Belt System, crosse over the study area. Three lines of imaging data and numerous magnetic data, encompassing the active thermal springs, were collected. Analysis of the geophysical data shows that the area is covered by low resistivity response regions at shallow depths which resulted from saline moisturized soil subsurface horizon. Relatively medium and high resistivity responses resulting from the weathered basalt, rhyolites, and ignimbrites are also mapped. Qualitative interpretation of the magnetic data shows the presence of structures that could act as pathways for heat and fluids manifesting as springs and also characterize the degree of thermal alteration of the area. Results from the investigations suggest that the Gergedi thermal springs area is controlled by fault systems oriented parallel and sub-parallel to the main tectonic lines of the Main Ethiopian Rift. Highlights: We collected electrical resistivity imaging and magnetic data over the Gergedi thermal springs. The data have been qualitatively interpreted and show the presence of structures, which could act as paths for heat and fluids for the manifested springs, and to characterize the degree of thermal alteration of the area. Result suggest the study area are controlled by fault systems oriented to the main tectonic line.